PENERAPAN ENTERPRISE RISK MANAGEMENT (ERM) DALAM TRANSFORMASI ORGANISASI PENGELOLA TABUNGAN PERUMAHAN - Puspita, Santi; Sparta (Ibs Press, 2025)
This study aims to analyze the implementation of BP Tapera's Enterprise Risk Management. This type of research is descriptive using qualitative and quantitative data obtained from primary and secondary data. Primary data were obtained by interviewing with purposive sampling at the job level KDK and BP Tapera’s Team Leader. Secondary data were obtained from the BP Tapera Strategic Plan, RKAT 2020 and supporting documents. Data analysis using the ERM framework, balanced scorecard, the ratio of Operating Costs to Operating Income (BOPO) and sensitivity analysis using crystall ball software. The results showed that: (1) The risks with the high risk category faced by BP Tapera were ineffective budget planning processes and the transfer of ex-Bapertarum funds was not according to the plan (2) The risk of an ineffective budget planning process has a significant impact on the achievement of strategic objectives, the availability of tools development and implementation of good governance with an efficient BOPO ratio and the risk of transferring ex-Bapertarum funds that are not in accordance with the plan has a moderate impact on strategic goals comprehensive, integrated, consistent, accountable, transparent and sustainable (3) Priority handling to minimize the risk of Ineffective Budget Planning Process, namely organizational design and completeness of gov ernance, preparation of physical infrastructure needs, implementation of Information Technology Systems to support services and operations, internal and external policies and regulations of BP Tapera, planning and ratification of RKAT , the design of the operating model for operations, and assessment and recruitment of human resources. Meanwhile, the priority of risk mitigation is to minimize the risk of Transfer of Funds Not according to Planning, namely the transfer of funds from former Bapertarum-PNS to BP Tapera, return of participant savings, and Migration & updating of membership data.